Inheritance of the Value of Peace in Post-Conflict Areas Based on Indigenous Knowledge - Aulia Rahman; Wasino Wasino; Mufti Riyani; Tengku Muhammad Sahudra; Bachtiar Akob (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study examines the inheritance of peace values based on indigenous knowledge in the community in Langsa after the Aceh conflict. Conflict causes damage to tolerance, respect for all forms of difference, and social capital due to disruption of the inheritance of values. If these problems are not addressed immediately, there is a risk of creating new patterns of conflict in the future. This study was conducted with a phenomenological qualitative approach. Data was collected through in-depth interviews, observation, and documentation. The data analysis technique used is descriptive qualitative analysis, while the data processing steps are data reduction, data display, and conclusions and data verification. This study found that indigenous knowledge framed in Islamic law was effective in transmitting the values of peace in post-conflict Aceh. The inheritance of the value of peace by using local resources can lead the community to values that maintain unity and tolerance. Utilizing local resources in passing on the value of post-conflict peace can maintain a peaceful situation and early detection of social conflicts.